Exploring the urban traffic space. Mapping the factors that affected the regulation and inspection of Lima’s urban transport system during the period 2007-2014 - Sánchez Flórez, Diego Alonso (2018)
This article aims to identify the different factors that have affected the recent urban transport policy of the local government of Lima, through the analysis of the Urban Transport Office (GTU) of the municipality of the metropolitan area of Lima (MML) during the period 2007-2014. The preliminary results emphasize the role of the sectorial and territorial governance of the urban transport, the urban transport stakeholders and the capacities of the governmental local agency dedicated to the inspection and regulation of the transport system in the city.